A study on the quality characteristics of red palm oil after frying / Mohamad Faizal Hajar Maidin - Hajar Maidin, Mohamad Faizal (2008)
The study was done on the quality characteristics of red palm oil after deep fat frying process in terms of chemical and physical changes as measured by percentage of peroxide value (PV), anisidine value (AV), free fatty acid (FFA), iodine value (IV), colour and viscosity. The study also determined the quality of food after deep frying process in red palm oil as determined by sensory evaluation. The frying process was done for five consecutive days at 165°C ± 5°C for both top up and non-top up oil. Based on the results obtained, top up oil had better quality in terms of PV, AV and FFA than non-top up oil. For IV, both oils showed the same trend which was the values decreased. For colour characteristics, the oils changed from dark red become light yellow after frying process. Meanwhile the viscosity of oil increased with days of frying. Sensory evaluation was conducted on food after frying process in terms of colour, aroma, taste and overall acceptability. Based on the results, only colour showed significant difference.